Determination of excitation functions for natBr(p,x) reactions with emphasis on the production of the radioisotope selenium-75 - De Villiers, Dawid (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.